DEGENERATIVE SYSTEM OF POPULAR SOVEREIGNTY BY POLITICAL PARTIES THROUGH THE INSTRUMENT OF THE RECALL RIGHTS - Malicia Evendia; Ade Arif Firmansyah (Law Faculty of Universitas Bandar Lampung, 2025)
The existence of the term